Estimation of stability of lifting equipment during excavation of pits in cramped conditions - N. S. Nikitina; N. K. Melnikov (Vestnik MGSU)
Introduction. The paper illustrates the necessity and place of the problem of stability assessment of lifting devices applied for excavation in cramped conditions, which are typical for urban areas with dense urban development when laying underground transport facilities on the example of the open method of works on the construction of the Moscow Metro.Materials and methods. Two sites on the territory of Moscow and different cranes of Liebherr company were considered in order to investigate the influence of geotechnical parameters on stability and safety of heavy lifting equipment. In addition, numerical modelling was carried out to determine displacements and deformations at different locations of the crane with respect to the excavation fence.Results. Horizontal and vertical displacements and total deformations of the pit fence were obtained by means of numerical modelling with the use of geotechnical software systems PLAXIS 2D and PLAXIS 3D. Among other things, we analyzed the usage of PAG slabs, as well as construction of the top tier of the spacing system with the use of 1.5 × 1.5 m inventory slabs.Conclusions. The relevant issue is an analytical calculation for situations that can arise in solving practical problems, in particular, in the development of the project of works for the installation of a lifting device near the pit with a fence. Surface layers of soils (up to 6 m) have a special and primary influence on the result of the calculation. If the lifting device is installed in bulk soil of natural origin, it is mandatory to replace it with a harder soil or to lay additional concrete slabs with a larger area to reduce the direct load on the ground. In special cases, the numerical modelling should be performed separately for heavy truck cranes with a lifting capacity of 250 tons and more, provided that the guardrail is made without a spacing system (“cantilever type”).